Development for academic leaders a practical guide for fundraising success - Hunt, Penelepe C., 1961-; Lippincott, John.; ebrary, Inc. (San Francisco : Jossey-Bass, 2012)
"Fundraising is an increasingly important responsibility for academic leaders, from department chairs to deans and on up into the executive ranks in higher education. In this book Penelepe Hunt (professional fundraiser, teacher, management consultant and executive coach) shows the vital role that academic leaders play in raising funds. She explains how leaders can learn the skills to become effective at networking, entrepreneurial, and productive fundraisers. This book offers a concise, practical guide to academic leaders succeed in their development activities. Hunt breaks down fundraising in a way that clarifies roles, responsibilities, programs, activities, politics, sources, and process.everything an academic leader needs to know in order to succeed"--
pt. 1. Development and academic leaders -- pt. 2. Development basics from an academic leader's perspective -- pt. 3. Development program components -- pt. 4. Special topics.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Educational fund raising -- United States; Electronic books